U.S. military operations : law, policy, and practice - Corn, Geoffrey S.; VanLandingham, Rachel E.; Reeve, Shane R.; McChrystal, Stanley A. (New York : Oxford University Press, 2015)
In this work, a distinguished group of military experts analyze how the law applies, and is applied, during military operations on and off the battlefield. The editors focus on how the law is operationalized, or actually implemented, in a wide swath of military activities.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on November 3, 2015).
Keywords: Military law -- United States; War (International law)